Cloud supersaturations from CCN spectra Hoppel minima. Issue 8 (24th April 2015) - Hudson, James G.; Noble, Stephen; Tabor, Samantha
Abstract High‐resolution cloud condensation nucleus (CCN) spectral measurements in two aircraft field projects, Marine Stratus/Stratocumulus Experiment (MASE) and Ice in Clouds Experiment‐Tropical (ICE‐T), often showed bimodality that had previously been observed in submicrometer aerosol size distributions obtained by differential mobility analyzers. However, a great deal of spectral shape variability from very bimodal to very monomodal was observed in close proximity. Cloud supersaturation (S) estimates based on critical S, Sc, at minimal CCN concentrations between two modes (Hoppel minima) were ascertained for 63% of 325 measured spectra. These cloud S were lower than effective S (Seff) determined by comparing ambient CCN spectra with nearby cloud droplet concentrations (Nc). Averages for the polluted MASE stratus were 0.15 and 0.23% and for the cumulus clouds of ICE‐T 0.44 and 1.03%. This cloud S disagreement between the two methods might in part be due to the fact that Hoppel minima include the effects of cloud processing, which push CCN spectra toward lower S. Furthermore, there is less cloud processing by the smaller cloud droplets, which might be related to smaller droplets evaporating more readily. Significantly lower concentrations within the more bimodal spectra compared with the monomodal spectra indicated active physical processes: Brownian capture of interstitial CCN and droplet coalescence. Chemical cloud processing also contributed to bimodality, especially in MASE.